2022
DOI: 10.3390/bs12110431
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Trauma Informed Care in Human Services: An Ecological Scoping Review

Abstract: Trauma and toxic stress are growing public health concerns with increasing risks to morbidity and mortality. Trauma informed care is an organizational response that challenges providers to adapt principled based approaches that seek to reduce adverse effects of care and support healing. However, there is a scarcity of empirical evidence on how trauma informed care is implemented in systems. A preferred reporting items for systematic reviews and meta-analysis-compliant scoping review based on Arksey, and O’Mall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…TIC is a framework for acquiring trauma knowledge and responses and supporting appropriate responses for traumatized individuals. TIC is offered in the community as well as in medical institutions ( Mahon, 2022 ) and can be applied in occupational health settings ( Rosemberg et al, 2017 ), as cognitive behavioral therapy that includes TIC has been reported to improve insomnia in PTSD ( Carlson et al, 2022 ), TIC could be practiced in occupational health settings to improve insomnia in workers with ACEs.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…TIC is a framework for acquiring trauma knowledge and responses and supporting appropriate responses for traumatized individuals. TIC is offered in the community as well as in medical institutions ( Mahon, 2022 ) and can be applied in occupational health settings ( Rosemberg et al, 2017 ), as cognitive behavioral therapy that includes TIC has been reported to improve insomnia in PTSD ( Carlson et al, 2022 ), TIC could be practiced in occupational health settings to improve insomnia in workers with ACEs.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It is, at its foundation, tied to language modeling insofar as individuals communicate their place within a larger community and vice versa. For example, EST has been used to discuss trauma-informed practices in educational contexts [27][28][29][30] and, by extension, its relevance for analyzing public health issues [25]. It has been used to analyze how individual students in certain group affiliations interact with schools [31,32].…”
Section: Emotional Intelligence Through the Lens Of Ecological System...mentioning
confidence: 99%
“…Systematic programs are needed to assist teachers in their emotional labor. More research is needed to design and test trauma-informed support programs that may be implemented school-wide [30,71].…”
Section: Group Did Not Demonstrate a Significant Change And Actually ...mentioning
confidence: 99%
“…There is a growing awareness that many persons who use human services may have previously experienced trauma and that to respond to such incidents, service delivery approaches may need to change (Mahon, 2022). Trauma-informed (TI) approach consists of various organizational cultures and practices that evaluate the occurrences and in uence of trauma on patients and the strategies employed by those healthcare services and professionals to avert further victimization (Emsley et al, 2022).…”
Section: Introductionmentioning
confidence: 99%